2021
DOI: 10.1155/2021/8850820
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells Enhance Therapeutic Effect and Prevent Adverse Gastrointestinal Reaction of Methotrexate Treatment in Collagen-Induced Arthritis

Abstract: Rheumatoid arthritis (RA) is a systemic autoimmune disease characterized by articular destruction and functional loss. Methotrexate (MTX) is effective in RA treatment. However, MTX induces several adverse events and 20%-30% of patients do not respond to MTX. Thus, it is urgent to enhance the therapeutic effects and reduce the side effects of MTX. Recent studies showed that mesenchymal stem cells (MSCs) were participants in anti-inflammation, immunoregulation, and tissue regeneration. However, whether the combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…Additionally, we have further shown that expression of key adipocytic genes C/EBPα and PPARγ considerably increased, indicating the adipogenic responses after MTX treatment. Our results support previous investigations (Fan et al, 2012; Georgiou et al, 2012; Marques et al, 2013; Zhai et al, 2021). Regulatory roles of miRNAs involved in controlling osteogenesis and adipogenesis have been studied under many pathological conditions (e.g., menopause and osteoporosis), however miRNAs that might be involved in MTX‐induced bone defects have not been characterized (H. G. Zhang et al, 2019; X. Zhang et al, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, we have further shown that expression of key adipocytic genes C/EBPα and PPARγ considerably increased, indicating the adipogenic responses after MTX treatment. Our results support previous investigations (Fan et al, 2012; Georgiou et al, 2012; Marques et al, 2013; Zhai et al, 2021). Regulatory roles of miRNAs involved in controlling osteogenesis and adipogenesis have been studied under many pathological conditions (e.g., menopause and osteoporosis), however miRNAs that might be involved in MTX‐induced bone defects have not been characterized (H. G. Zhang et al, 2019; X. Zhang et al, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…Cytokine shifts play key roles in inflammation, synovial hyperplasia, and cartilage and bone destruction; hence, decreases in inflammatory cytokine levels and elevated levels of anti‐inflammatory cytokines can reduce clinical symptoms of arthritis (Shu et al., 2015; Zhai et al., 2021). We investigated the level of pro‐ and anti‐inflammatory cytokines in the sera of the rat RA model.…”
Section: Discussionmentioning
confidence: 99%
“…In the process of inflammation, M1 macrophages secrete IL-6 and IL-1β 50 . M2 macrophages secrete IL-10 and produce an anti-inflammatory microenvironment 51 . Therefore, we measured the ratio of M1/M2 macrophages in mouse kidneys using the Flow cytometry method.…”
Section: Discussionmentioning
confidence: 99%